2016
DOI: 10.1016/j.jmoldx.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colorectal Cancer Using a Simplified SEPT9 Gene Methylation Assay Is a Reliable Method for Opportunistic Screening

Abstract: SEPT9 gene methylation was validated as a biomarker for colorectal cancer (CRC) for >10 years and available as the Epi proColon test as an aid in CRC detection for >6 years. It was proven to be an accurate, reliable, fast, and convenient molecular test. In this opportunistic screening study, we validated a further simplified SEPT9 gene methylation assay in 1031 subjects in Chinese hospitals. The sensitivity for CRC detection was 76.6% at a specificity of 95.9%, and the results showed a satisfactory detection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 29 publications
4
113
1
Order By: Relevance
“…Regarding the use of gene promoter methylation as CRC biomarker, the best detection performance was disclosed by SEPT9 promoter methylation, followed by MGMT. Remarkably, SEPT9 validity estimates were similar to those of the trademark assays using SEPT9 methylation [12,35], further confirming its biomarker potential. Nonetheless, MGMT displayed better performance (77.2% sensitivity, 84.0% specificity) than previously reported (46-53% sensitivity, 74-100% specificity), especially concerning sensitivity [23,36].…”
Section: Discussionsupporting
confidence: 63%
“…Regarding the use of gene promoter methylation as CRC biomarker, the best detection performance was disclosed by SEPT9 promoter methylation, followed by MGMT. Remarkably, SEPT9 validity estimates were similar to those of the trademark assays using SEPT9 methylation [12,35], further confirming its biomarker potential. Nonetheless, MGMT displayed better performance (77.2% sensitivity, 84.0% specificity) than previously reported (46-53% sensitivity, 74-100% specificity), especially concerning sensitivity [23,36].…”
Section: Discussionsupporting
confidence: 63%
“…We recently tested this assumption in an opportunistic screening setting, in which blood and stool samples were collected from outpatients and inpatients coming to the GI departments of three Chinese hospitals[55]. Table 6 shows the test results from the screening.…”
Section: Crc Screening With Combined Testsmentioning
confidence: 99%
“…Test performance (Table 1) was evaluated in a number of case control studies in Europe and China [27,[31][32][33][34]. As outlined in these studies, test sensitivity was reported to range from 73-81% and test specificity was reported to range from 96-99%.…”
Section: Epi Procolon 20 and The Us Fda Pma Approved Epi Procolonmentioning
confidence: 99%
“…As outlined in these studies, test sensitivity was reported to range from 73-81% and test specificity was reported to range from 96-99%. A modified version of this test was developed in China, and tested in an opportunistic screening setting [34].…”
Section: Epi Procolon 20 and The Us Fda Pma Approved Epi Procolonmentioning
confidence: 99%